1994
DOI: 10.1111/j.1525-1314.1994.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction textures and fluid behaviour in very high pressure calc‐silicate rocks of the Münchberg gneiss complex, Bavaria, Germany

Abstract: Reaction textures and fluid behaviour in very highABSTRACT Calc-silicate rocks occur as elliptical bands and boudins intimately interlayered with eclogites and high-pressure gneisses in the Munchberg gneiss complex of NE Bavaria. Core assemblages of the boudins consist of grossular-rich garnet, diopside, quartz, zoisite, clinozoisite, calcite, rutile and titanite. The polygonal granoblastic texture commonly displays mineral relics and reaction textures such as postkinematic grossular-rich garnet coronas. React… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Framboidaltextured titanites are always developed around a prismatic rod of rutile or ilmenite and composed of numerous tiny subhedral prisms of titanite (Fig. 2b), this type of texture being a common decompression texture in high-P rocks (Klemd et al 1994;Frost et al 2000;Bingen et al 2001). This distinctive texture is heterogeneously developed and primarily reflects the distribution of host rutile or ilmenite crystals.…”
Section: U-pb and Pb-pb Systematics Of Titanite And Plagioclasementioning
confidence: 97%
“…Framboidaltextured titanites are always developed around a prismatic rod of rutile or ilmenite and composed of numerous tiny subhedral prisms of titanite (Fig. 2b), this type of texture being a common decompression texture in high-P rocks (Klemd et al 1994;Frost et al 2000;Bingen et al 2001). This distinctive texture is heterogeneously developed and primarily reflects the distribution of host rutile or ilmenite crystals.…”
Section: U-pb and Pb-pb Systematics Of Titanite And Plagioclasementioning
confidence: 97%
“…Studies of other HP-UHP belts revealed that some metasedimentary rocks also experienced HP to UHP metamorphism and shared a common metamorphic history with the enclosed/interlayered eclogites (e.g. Compagnoni, Rolfo, & Castelli, 2012;Gross, Burchard, Schertl, & Maresch, 2008;Klemd, Matthes, & Okrusch, 1991;Klemd, Matthes, & Sch€ ussler, 1994;Klemd et al,1991;Spear & Franz, 1986).…”
Section: Was the Uhp Sub-belt A Coherent Unit?mentioning
confidence: 99%
“…The MMC is regarded as a nappe pile transported on top of autochthonous, anchi-metamorphic Palaeozoic sequences of the Thuringian lithofacies, as exposed in the southeastern Frankenwald, in the Lower Carboniferous (Franke, 1984;Klemd et al, 1994;Klemd, 2010). This nappe pile is subdivided from the bottom to the top into the following units: Prasinit-Phyllit, Rand-Amphibolit, Liegendserie, and Hangendserie (e.g.…”
Section: Geological Settingmentioning
confidence: 99%
“…The peak P-T conditions of these eclogites were estimated by several studies (Franz et al, 1986;Klemd, 1989;Klemd et al, 1991Klemd et al, , 1994O'Brien, 1993;Liebscher et al, 2007). These conditions cluster in the P-T range of 20-34 kbar and 550-750°C.…”
Section: Geological Settingmentioning
confidence: 99%